Telecommunication and the allocation of scarce resources and / or essential facilities in terms of the Competition Act 98 of 1998 of South Africa - Van Heerden, C.M. (Corlia) (University of Pretoria, 2014)
Dissertation LLM --University of Pretoria, 2014